2012
DOI: 10.1111/j.1349-7006.2012.02214.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of MUC16 and mesothelin is related to the invasion process in pancreatic ductal adenocarcinoma

Abstract: The invasion process is a crucial step for pancreatic ductal adenocarcinoma (PDAC); however, the genes related to invasion remain unclear. To identify specific genes for the invasion process, we compared microarray data for infiltrating cancer and PanIN-3, which were harvested from an individual PDAC patient by microdissection. Furthermore, immunohistochemical, coimmunoprecipitation and invasion analyses were performed to confirm the biologic significance of molecules identified by expression profile. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 27 publications
(49 reference statements)
6
69
0
Order By: Relevance
“…In this study, we confirmed that mesothelin expression is a prominent prognostic factor for EHBDCA patients as well as for other tumors such as pancreatic cancer and ovarian carcinoma described previously (12,15,23). Furthermore, we revealed that the expression pattern of mesothelin, in luminal membrane or cytoplasm, could be a more evident prediction factor for these patients.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we confirmed that mesothelin expression is a prominent prognostic factor for EHBDCA patients as well as for other tumors such as pancreatic cancer and ovarian carcinoma described previously (12,15,23). Furthermore, we revealed that the expression pattern of mesothelin, in luminal membrane or cytoplasm, could be a more evident prediction factor for these patients.…”
Section: Discussionsupporting
confidence: 89%
“…MSLN is expressed in several human malignancies, including mesotheliomas and ovarian cancer. Studies of patients with ovarian cancer have identified the cancer antigen CA125 as an MSLN ligand (20)(21)(22)(23), which is widely used as a diagnostic marker (with the exception of pregnancy and liver cirrhosis, which are considered false-positives) (24). Since high expression of MSLN is linked to increased tumor proliferation and invasion, MSLN is a novel Cholestatic liver fibrosis is caused by obstruction of the biliary tract and is associated with early activation of portal fibroblasts (PFs) that express Thy-1, fibulin 2, and the recently identified marker mesothelin (MSLN).…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in Table 3, "high-level expression" was detected in 45 cases (49.5 %), whereas "low-level expression" was detected in 46 cases (50.5 %), although "high-level expression" of mesothelin was not correlated with clinicopathological parameters such as histological grade, T-factor and metastasis. Recent studies reported that higher mesothelin expression was found to be associated with shorter patients' survival in ovarian and pancreatic cancer [31][32][33]; therefore, we also examined the correlation of mesothelin overexpression with overall survival (OS) in the CRC patients. Contrary to our expectation, the group of "high-level expression" of mesothelin was not correlated with OS compared to the group of "low-level expression" of mesothelin (P = 0.26, Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%